Fluxional dynamics of terpyridine ligand in [Ru(bpy-d8)2(η2-tpy)]2+ complex - Rahman, MA; Rajbangshi, S (Bangladesh Journal of Scientific and Industrial Research, 2020)
Herein, we report the fluxional dynamic behaviour of terpyridineligand in [Ru(bpy-d8)(η2-tpy)]2+ 1. Reaction of Ru(bpy-d8)2Cl2·2H2O with 2,2′:6′,2′′-terpyridine in refluxing methanol afforded 1. Complex 1 has been characterized by 1H NMR spectroscopic analysis. Variable temperature 1H NMR data reveals that the pendant pyridine ring of the tpy ligand in Ru(bpy-d8)2(tpy)]2+ rotates which effects the adjacent ring protons. Moreover, protonation of 1 with trifluoroacetic acid (TFA) confirms that peripheral N on the pendant pyridyl ring of the tpy ligand affects the chemical shifts of protons on the tpy pendant pyridyl ring. Bangladesh J. Sci. Ind. Res.55(4), 253-260, 2020